Водно-міграційні властивості дизельного палива у чорноземному ґрунті - Шевченко, О.А.; Кулагін, О.О. (Актуальні проблеми транспортної медицини, 2016)
В роботі в лабораторному експерименті вивчено особливості вертикальної міграції та порогової концентрації дизельного палива (ДП) на прикладі чорнозему малогумусного середньозмитого для його подальшого гігієнічного регламентування за міграційно-водним показником шкідливості.
Встановлено, що при концентрації ДП в чорноземі типовому 3000, 6000, 10000 та 13000 мг/кг його концентрації у фільтраті в продовж експерименту коливалися в межах від 0,055-0,071; 0,124-0,193; 0,198-0,235 та 0,256-0,298 мг/дм³ відповідно. При концентраціях ДП у чорноземі типовому на рівні 17 000 мг/дм³ та 20000 мг/дм³ його максимальний вміст у фільтраті становив 0,501 мг/дм³ та 1,430 мг/дм³, що перевищувало ГДК НП для води водойм. В результаті експериментального вивчення процесів вертикальної міграції ДП у чорноземі малогумусному середньозмитому його порогову концентрацію встановлено на рівні 13000 мг/кг. В лабораторном эксперименте определяли особенности вертикальной миграции и пороговой концентрации дизельного топлива (ДТ) на примере чернозема малогумусного среднесмытого для его дальнейшей гигиенической регламентации по миграционно-водным показателям вредности. Для проведения лабораторного эксперимента использовали модификацию классической методики Э.И. Гончарука. Изучение миграции ДТ в системе „почва — грунтовые води” осуществляли в
фильтрационных колонах с черноземом типичным. В фильтрационные колоны подавали среднюю половину нормы воды из расчета на среднегодовое количество
осадков в Днепропетровской области. После накопления фильтрата объемом 1
дм³ определяли содержание ДТ по методике МВВ 99712798. В результате экспериментального изучения процессов вертикальной миграции ДТ в черноземе малогумусном среднесмытом его пороговою концентрация установлено на уровне
13000 мг/кг. Aim of the research – defining peculiarities of vertical migration and threshold concentration of disel oil (DO) in laboratory experiment by the example of lowhumic chernozem for its further hygienic regulation by migration-water index of its hazard.
Materials and methods. To perform laboratory experiment there was used modification of a classic procedure by Ye. І. Honcharuk. Studying of DO migration in the system „ground – ground waters” was done in filtration pipes with typical chernozem. Into filtration pipes there was pumped average watering rate on the basis of average annual amount of precipitations in Dnipropetrovs’k region. After accumulation of filtrate in the volume of 1 dm3 there was defined content of DO by the procedure МВВ 99-12-98.
Research results. It was defined that in concentration of DO 3000, 6000, 10000 and 13000 mg/kg in the typical chernozem, its concentrations in the filtrate during the experiment ranged within the limits from 0,055-0,071; 0,124-0,193; 0,198-0,235 and
0,256-0,298 mg/dm³ correspondingly. In concentrations of DO in the typical chernozem at the level of 17 000 mg/kg and 20000 mg/kg, its content in the filtrate was 0,501 mg/dm³ and 1,430 mg/dm³, this did not exceed MPC of petroleum products (PP) for the water of reservoirs.
Conclusions. Resulting from experimental studying of processes of vertical migration of DO in low-humic chernozem, its threshold concentration was defined to be at the level of 13000 mg/kg.